AUDIT DAN ANALISIS PENGHEMATAN ENERGI SISTEM TATA CAHAYA GEDUNG E DAN GEDUNG F DI POLITEKNIK NEGERI CILACAP - Fadhillah Hazrina; Vicky Prasetia; Afrizal Abdi Musyafiq (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2020)
The purpose of this study was to conduct a review of energy audits in the lighting systems of building E and F of the Cilacap State Polytechnic. The results of the calculation of energy audits in lighting can be used as a guideline to make efficiency in the use of electrical energy. The initial step taken in this study was to look for primary and secondary data. Primary data is obtained by making direct measurements in all building rooms E and F. Secondary data obtained from relevant agencies such as the Cilacap State Polytechnic building data; energy demand data from the Energy and Mineral Resources (ESDM) Office; and data on electricity consumption from the National Electricity Company (PLN). The data is then processed to obtain the value of Energy Use Intensity (IKE) and can also be used as a guide for carrying out measures in energy efficiency. Based on the calculation and processing of the data obtained, the energy consumption of buildings E and F is 3,259.82 kWh/month and 3,650.96 kWh/month. The results of the energy audit calculations performed on the building lighting systems E and F with a building area of ??287 m2 and 399 m2 have a building IKE value of 11.37 kWh/ m2/month and 9.16 kWh/m2/month. Based on the IKE criteria index, it was found that building E and F of the State Polytechnicof Cilacap were included in the criteria of efficiency.